A mixed-methods feasibility study of dog-assisted exercise therapy in geriatric inpatients - Lilly Joschko; Eva Jansen; Stefanie Weinert; Maximilian Hinse; Roland Zerm; Harald Matthes (BMC Geriatrics, 2026)
Abstract Background Animal-assisted therapy (AAT) is a promising complementary approach in geriatric rehabilitation, but evidence on feasibility and patient experiences remains limited. Methods This exploratory, mixed-methods, two-arm randomized controlled parallel-group design (RCT) compared dog-assisted exercise therapy (intervention) to standard exercise therapy (active control) in geriatric inpatients during a two-week rehabilitation program. Quantitative data on mobility (TUG), depression (HADS-D) symptoms, motivation (VAS), and satisfaction (VAS)were collected and analysed using descriptive statistics, cross-tabulations, group comparisons (unpaired t-test or Mann–Whitney U test), and correlation (Spearman’s ρ). Semi-structured interviews explored patientsexperiences. Data were analyzed separately and integrated using a joint display approach. Results 27 patients participated in the RCT, and 11 in the embedded qualitative study. Quantitative measures showed no clinically meaningful between-group differences in mobility or depressive symptoms: mobility (TUG) (control: Mdn = 16.00, IQR [14.25, 22.50]; intervention: Mdn = 18.00, IQR [13.00, 20.50]); depression (HADS-D) = 0.2 points (95% CI [–3.2, 3.6], SD = 3.05). Motivation and satisfaction were consistently high across conditions. A strong positive correlation was observed between motivation and satisfaction (ρ = 0.65, p < .001). Qualitative results indicated high acceptance and feasibility, enhanced emotional well-being, motivation, social interaction, and engagement, particularly associated with the presence of the therapy dog. Mixed-methods integration indicated high feasibility and acceptability of the intervention. Qualitative findings complemented the quantitative results by demonstrating that the therapy dog enhanced the ward atmosphere and patient engagement, despite the absence of measurable short-term clinical changes. Limitations Key limitations include novelty effects, the dog’s visibility across conditions, the influence of prior pet ownership, COVID-19, dropouts, small sample size, the awareness of the presence of the dog at ward for the control group, and a heterogeneity group of conditions. These factors may have impacted the overall outcomes. Conclusion Animal-assisted exercise therapy is feasible and well accepted in geriatric inpatient care. Its primary benefits appear to be experiential and psychosocial, supporting engagement and rehabilitation participation rather than immediate clinical improvement. Further research should investigate long-term effects and underlying mechanisms. Trial registration This study has been registered in the German Clinical Trial Registry with trial ID DRKS00024955 on 22 April 2021 and was approved by the ethics committee (EA4/071/21).